2021
DOI: 10.18632/aging.203483
|View full text |Cite
|
Sign up to set email alerts
|

MiR-185-5p targets RAB35 gene to regulate tumor cell-derived exosomes-mediated proliferation, migration and invasion of non-small cell lung cancer cells

Abstract: Introduction: Non-small cell lung cancer (NSCLC) is the most common malignant tumor, and its recurrence and metastasis are the main causes of death. Recently, there is evidence that tumor derived exosomes play an important role in the occurrence and development of NSCLC. Objective’s methods: First, the expression of miR-185-5p and RAB35 in NSCLC tissues, paracancerous tissues, NSCLC cell lines and normal human bronchial epithelial cell line was detected. Then, a series of gain-and loss-of-function a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“… 33 Studies had demonstrated that hsa-miR-183-5p could inhibit the proliferation, migration and invasion of non-small cell lung cancer cells by down-regulating the expression of RAB35 and KLF7. 48 , 49 The 3 biomarkers (HLA-DMB, PPIA, GPI) were associated with hsa-miR-135a-5p and hsa-miR-183-5p, suggesting that these biomarkers have therapeutic potential for LUAD.…”
Section: Discussionmentioning
confidence: 97%
“… 33 Studies had demonstrated that hsa-miR-183-5p could inhibit the proliferation, migration and invasion of non-small cell lung cancer cells by down-regulating the expression of RAB35 and KLF7. 48 , 49 The 3 biomarkers (HLA-DMB, PPIA, GPI) were associated with hsa-miR-135a-5p and hsa-miR-183-5p, suggesting that these biomarkers have therapeutic potential for LUAD.…”
Section: Discussionmentioning
confidence: 97%
“…For example, miRNA-185-5p inhibits the proliferation, migration, and invasion of non-small cell lung cancer cells by targeting RAB35. 25 In glioma, circPOSTN promotes tumor progression by acting as a miR-185-5p sponge to upregulate KIF1B expression. 26 In TNBC, the expression of circRNA-CREIT was decreased in doxorubicin resistant TNBC cells and associated with a poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several dysregulated miRNAs are involved in the pathogenesis of lung cancer by affecting cell proliferation, apoptosis, migration, and metastasis [ 19 ]. Through genome-wide investigation and analysis, a set of miRNAs were found to be deregulated in the tissues of lung cancer patients with BM, and a group of miRNAs are closely correlated to prognosis and can be used as diagnostic biomarkers [ 20 , 21 ]. Although the role of miRNAs in regulating BM has been indicated, the underlying molecular mechanism is still poorly understood, especially in lung cancer.…”
Section: Introductionmentioning
confidence: 99%